2015
DOI: 10.3389/fnins.2015.00032
|View full text |Cite
|
Sign up to set email alerts
|

Development of the choroid plexus and blood-CSF barrier

Abstract: Well-known as one of the main sources of cerebrospinal fluid (CSF), the choroid plexuses have been, and still remain, a relatively understudied tissue in neuroscience. The choroid plexus and CSF (along with the blood-brain barrier proper) are recognized to provide a robust protective effort for the brain: a physical barrier to impede entrance of toxic metabolites to the brain; a “biochemical” barrier that facilitates removal of moieties that circumvent this physical barrier; and buoyant physical protection by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
167
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(171 citation statements)
references
References 133 publications
1
167
0
3
Order By: Relevance
“…35 Indeed, tight junctions of the blood-CSF barrier are more permeable than those of the blood-brain barrier. 36,37 Moreover, Jost et al 38 recently demonstrated T1 enhancement in the CSF 1 minute after a single injection of all categories of GBCAs in rats, and Naganawa et al 39 reported T1 enhancement in the CSF after injection of a single dose of gadoteridol in healthy volunteers, from 1.5 hours postinjection, increasing until 3 hours postinjection, and then slowly decreasing. The DCN are adjacent to the CP of the fourth ventricle and are particularly rich in metals such as iron, copper, and zinc.…”
Section: Discussionmentioning
confidence: 99%
“…35 Indeed, tight junctions of the blood-CSF barrier are more permeable than those of the blood-brain barrier. 36,37 Moreover, Jost et al 38 recently demonstrated T1 enhancement in the CSF 1 minute after a single injection of all categories of GBCAs in rats, and Naganawa et al 39 reported T1 enhancement in the CSF after injection of a single dose of gadoteridol in healthy volunteers, from 1.5 hours postinjection, increasing until 3 hours postinjection, and then slowly decreasing. The DCN are adjacent to the CP of the fourth ventricle and are particularly rich in metals such as iron, copper, and zinc.…”
Section: Discussionmentioning
confidence: 99%
“…Because the cerebellum is located adjacent to the fourth ventricle and the cerebral ventricles are partly surrounded by the choroid plexus in young children (Su and Young, 2011;Liddelow, 2015), impaired cellular metal homeostasis probably induces hyperactivation of the cerebellum via dysfunction of choroid plexus and fourth ventricle in young children with ASD. Neuronal hyperactivation can trigger M1 polarization of microglia in the cerebellum, and then M1 microglial-mediated neuroinflammation and neural network dysfunction may extend to the related tissues under inhibition in the M2 state.…”
Section: Social Cognitive Deficits In Asdmentioning
confidence: 99%
“…Different from BBB, the capillary cells of the BCSFB do not have tight junctions, and they are fenestrated allowing for free permeation of various substances [142]. Circumscribing these capillaries are polarized epithelial cells with tight junctions, preventing free diffusion between blood and surrounding CSF.…”
Section: Covalent Nanodelivery Systems For Imaging and Treatment Omentioning
confidence: 99%